Selected issues concerning oral health in female patients with eating disorders: a survey study - Mazurek Mateusz; Szyszkowska Anna; Mazurek Agata; Szymanska Jolanta (Current Issues in Pharmacy and Medical Sciences, 2016)
The study aimed to evaluate behaviours relevant to oral health and the condition of the teeth and gums in women with eating disorders. A survey study covered a group of 30 patients aged 14-36 years suffering from diagnosed eating disorders and treated in closed psychiatric wards. The control group included 30 healthy women at the mean age corresponding to that of the patient group. The questions concerning oral health-relevant behaviours referred to the frequency of tooth brushing and the kind of toothbrush used, the frequency of dental visits, fear of dental visits, and self-evaluation of the selected items of oral health status. The survey results were analysed statistically. Behaviours relevant to oral health in women with eating disorders include increased oral hygiene and the attitude to dental visits that does not diverge from the customary one. The patients found the presence of enamel damage to be as frequent as in the healthy subjects. Eating disorders are, however, conducive to more frequent gum disorders and the feeling of dryness in the mouth.